Workplace skills in practice : case studies of technical work - Stasz, Cathleen, 1947-; Ramsey, Kimberly; Eden, Rick, 1954-; Melamid, Elan.; Kaganoff, Tessa; Rand Corporation; Rand Institute on Education & Training; National Center for Research in Vocational Education (U.S.) (Santa Monica, CA : RAND, 1996)
Many believe that the workplace has changed in ways that require workers with higher and more varied skills--and that schools are not producing students with such skills. In this study, the authors sought to better understand skills required in technical work, the institutional context in which work takes place, and employers' strategies for meeting perceived skill requirements. The study used a sociocultural approach to examine skills and work-related dispositions (tendencies to use one's capabilities on the job) in four diverse industries. A rich picture emerged, demonstrating that work context matters in the consideration of skills: workplaces are complex, dynamic social systems that defy simplistic categorization of skills and straightforward matching of skill requirements to jobs. The study also found that employers do not necessarily understand the skills required, especially for frontline workers, nor adopt effective strategies for identifying and developing those skills. For example, employers have few connections to education providers and do not fully utilize industry skill certification. These and other findings raise questions about current public policy on school reform and skill standards.
Includes bibliographical references (p. 113-122).
Also available on the internet via WWW in PDF format.
Keywords: Labor market -- United States; Labor supply -- Education (Secondary) -- United States; Labor supply -- United States -- Attitudes; Occupational training -- United States -- Case studies; Skilled labor -- United States